Validation of construct, content and reliability of process-type indicators used for the assessment of curricular process dimension at higher education: the case of Costa Rica Institute of Technology - Lira-Valdivia, Rosa Inés (2014)
This paper is a part of a dissertation carried out as a doctoral study with the University of Valencia, to design Process-type-items for the assessment of Curriculum Process Dimension in Higher Education. Methodologically these indicators have been validated by a research evaluation based on expert judgment using a quantitative approach. This series of indicators has been built for Costa Rica Institute of Technology. The outcomes of three types of vali-dity: construct, content and reliability are shown in this article. It is considered that the results achieved, provide sufficient evidence to support the proposed Process-type Indicators, as widely trusted and as quality items to provide valid and reliable information in assessing Curriculum Process Dimension. These indicators will also provide relevant data for making educational policy decisions in the area of curriculum development.